(untitled) (Sains Humanika, 2019)
This study aims to analyse the water usage practices difference based on gender among Form Four students in Northern Kinta district, Perak. This study used quantitative (survey) method and involved a sample of 420 students who are selected using a stratified random sampling method from thirteen schools. The data were collected through a questionnaire which focuses on the five aspects of the variables namely knowledge, values, skills, attitudes and practices of sustainable usage of water. Inferential analysis (t-test) is used to answer the objective of the study. The findings of the t-te`st analysis show that there is no significant difference in terms of knowledge, values, skills and practices of sustainable usage of water based on students’ gender. Furthermore, the t-test analysis showed that there was a significant difference in the attitude of water consumption between male and female students. This shows that there is no difference in the practice of water usage among students based on gender. Nevertheless, aspects of attitudes need to be addressed so that male and female students are always positive towards water saving practices in order to achieve sustainable water management.